2017
DOI: 10.1002/etc.3948
|View full text |Cite
|
Sign up to set email alerts
|

Acute exposure to an environmentally relevant concentration of diclofenac elicits oxidative stress in the culturally important galaxiid fish Galaxias maculatus

Abstract: Diclofenac is a nonsteroidal anti-inflammatory drug (NSAID) of growing concern in aquatic environments worldwide; nevertheless, knowledge of its effects on aquatic biota is restricted to a few model species with limited information regarding its mechanisms of impact. In the present study, diclofenac accumulation, its effects on metabolic rate, ionoregulation, and oxidative stress were examined at environmentally relevant (0.17 mg L À1 ) and elevated (763 mg L À1 ) concentrations in a culturally and economicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…The inhibition of CAT activity may be due to the binding of the antibiotic to the thiol group, which may possibly increase hydrogen peroxide and superoxide radicals 19 . McRae et al 51 reported that the decrease in the gill CAT activity of fish ( Galaxias maculates ) indicates impaired CAT activity in the gill due to drug toxicity. Acceleration of GST activity was observed in fish species exposed to various pharmaceuticals, specifically quinolone, 52 and ciprofloxacin (0.7 and 100 g/L) concentrations 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition of CAT activity may be due to the binding of the antibiotic to the thiol group, which may possibly increase hydrogen peroxide and superoxide radicals 19 . McRae et al 51 reported that the decrease in the gill CAT activity of fish ( Galaxias maculates ) indicates impaired CAT activity in the gill due to drug toxicity. Acceleration of GST activity was observed in fish species exposed to various pharmaceuticals, specifically quinolone, 52 and ciprofloxacin (0.7 and 100 g/L) concentrations 17 .…”
Section: Discussionmentioning
confidence: 99%
“…An increase in LPO levels (in R. subcapitata ) to antibiotics (sulfamethoxazole and erythromycin) indicates the failure of antioxidants or that increased antioxidant response was not enough to neutralize the accumulation of ROS and to prevent cellular oxidative damage 48 . McRae et al 51 reported that when CAT activity decreased, the LPO level may increase. Our study also confirms that conclusion, and we also noticed the elevated level of LPO activity and the decline of CAT activity in ciprofloxacin exposed fish.…”
Section: Discussionmentioning
confidence: 99%
“…Observations of antibiotic resistance of bacteria [30,[126][127][128][129][130], intersex occurrence in freshwater fish [31,[131][132][133], and oxidative stress in aquatic organisms [134][135][136][137] are major adverse effects from CECs in the water cycle [138]. Many researchers have investigated the effect of the wastewater treatment processes on the prevalence of antibiotic-resistant bacteria in the plants and receiving waters [126,128,129].…”
Section: Adverse Effects From Cecsmentioning
confidence: 99%
“…At greater concentrations of 3.00 and 9.00 µg/L, a significant decrease in the antioxidant enzymes was observed and led to the impairment of the ability to cope with oxidative stress. Similarly, in galaxiid fish, an acute exposure to 0.17 µg/L of diclofenac for 96 h resulted in a decrease in catalase activity in the gill tissue [135]. Stancova et al (2017) evaluated the early stages of oxidative stress in Tench fish exposed to environmentally relevant concentrations (0.02-60 µg/L) of ibuprofen, diclofenac, and carbamazepine [137].…”
Section: Adverse Effects From Cecsmentioning
confidence: 99%
“…Research Article (Echeverria-Saenz et al, 2018;Jiang et al, 2018;Lungu-Mitea et al, 2018;McRae et al, 2018;Rather et al, 2018;Vicari et al, 2018;Zhang et al, 2018).…”
Section: Araştırma Makalesimentioning
confidence: 99%